2020 IEEE/RSJ International Conference on Intelligent Robots and Systems (IROS) 2020
DOI: 10.1109/iros45743.2020.9341353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Transfer of Human Movement Manipulability in Industry-like Activities

Abstract: Humans exhibit outstanding learning, planning and adaptation capabilities while performing different types of industrial tasks. Given some knowledge about the task requirements, humans are able to plan their limbs motion in anticipation of the execution of specific skills. For example, when an operator needs to drill a hole on a surface, the posture of her limbs varies to guarantee a stable configuration that is compatible with the drilling task specifications, e.g. exerting a force orthogonal to the surface. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In that work, a profile of the manipulability ellipsoid was used to control a humanoid robot. Building on that method, Jaquier et al later showed [84] that the manipulability ellipsoid was task-dependent, and it could be transferred to robots for human-like movement. Sentis et al [85] showed that it was possible to use the gradient projection to apply multiple criteria recursively to refine the performed motion.…”
Section: Gradient Projection Methodsmentioning
confidence: 99%
“…In that work, a profile of the manipulability ellipsoid was used to control a humanoid robot. Building on that method, Jaquier et al later showed [84] that the manipulability ellipsoid was task-dependent, and it could be transferred to robots for human-like movement. Sentis et al [85] showed that it was possible to use the gradient projection to apply multiple criteria recursively to refine the performed motion.…”
Section: Gradient Projection Methodsmentioning
confidence: 99%
“…Such mappings were manually defined for similar kinematics [21] or learned automatically from data [28]. To bypass the complexity of these mappings, several works instead focused on transferring the functional part of the motion by mapping endeffector trajectories [29] or manipulability patterns [30].…”
Section: Riemannian Motion Transfermentioning
confidence: 99%